Subsequent maternal sleep deprivation aggravates neurobehavioral abnormalities, inflammation, and synaptic function in adult male mice exposed to prenatal inflammation - Zhang, Yue-Ming; Zhang, Meng-Ying; Wei, Ru-Meng; Zhang, Jing-Ya; Zhang, Kai-Xuan; Luo, Bao-Ling; Ge, Yi-Jun; Kong, Xiao-Yi; Li, Xue-Yan; Chen, Gui-Hai (Frontiers in Behavioral Neuroscience, 2023)
Objective: Studies have suggested that prenatal exposure to inflammation increases the risk of neuropsychiatric disorders, including anxiety, depression, and cognitive dysfunction. Because of anatomical and hormonal alterations, pregnant women frequently experience sleep dysfunction, which can enhance the inflammatory response. The aim of this study was to explore the effects of maternal sleep deprivation on prenatal inflammation exposure-induced behavioral phenotypes in offspring and identify the associated mechanisms. Methods: Pregnant mice received an intraperitoneal injection of lipopolysaccharide (LPS) on gestational day 15 and were subsequently subjected to sleep deprivation during gestational days 15-21. Anxiety-like behavior was evaluated by the open field test and the elevated plus maze test. Depression-like behavior was assessed by the tail suspension test and the forced swimming test. Cognitive function was determined using the Morris water maze test. The levels of markers of inflammation and synaptic function were examined employing general molecular biological techniques. Results: The results showed that prenatal exposure to LPS resulted in anxiety-and depression-like symptoms and learning and memory deficits, and these effects were exacerbated by maternal sleep deprivation. Furthermore, maternal sleep deprivation aggravated the prenatal LPS exposure-induced increase in the expression of interleukin (IL)-1β, IL-6, and tumor necrosis factor-α and decrease in the levels of postsynaptic density-95 and synaptophysin in the hippocampus. Discussion: Collectively, these results suggested that maternal sleep deprivation exacerbates anxiety, depression, and cognitive impairment induced by prenatal LPS exposure, effects that were associated with an inflammatory response and synaptic dysfunction.